PROBLEMATIKA PENANGANAN ILLEGAL LOGGING - Fadliah . (JURNAL LEGALITAS, 2009)
Indonesia as world power, can be considered to be one of world lung becouse besides wes own wide sea, indonesia also has the biggest forest area. but we also is state experiencing highest deforestation speed. logging problem of this wild very difficult to be fought against by its(the mafia works very nice. Besides destruction of ecosystem and damage of other nature, practice of illegal logging also makes we are losing of around 5 billion dollars or aroun 50 triliyun rupiah per year. to take care of continuity of forest from irresponsible hands of department of Forestry ought to\'cooperate with police and public does eradication to illegal of logging or wild logging.